Infection by Zika Vírus in human cells alters the expression profile of miRNA-15 and activation of apoptotic caspases (Research, Society and Development, 2020)
Objective: Evaluate the miRNA-15 expression profile involved in cellular apoptotic regulation factors. Methodology: We used the H818308 Asian strain of ZIKV without neurological damage. The inoculations occurred in human embryonic kidney cells (HEK-293). After inoculation, samples were extracted for RT-qPCR quantification of viral RNA and miR-15. The level of activation of caspases 1, 3/7 and 8 of cells was performed using chemofluorescence. Results: The ZIKV infection alters the expression of genes and their regulators, affecting several cellular physiological processes such as apoptosis. Conclusion: Therefore, it is important to emphasize that renal progenitor cells (HEK-293) are susceptible to VZIK infection. The genetic deregulation resulting from infection directly affects important cellular processes such as apoptosis from the disordered miRNA-15 expression during the infection period.